2002
DOI: 10.1093/gerona/57.8.m539
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-Stand Performance Depends on Sensation, Speed, Balance, and Psychological Status in Addition to Strength in Older People

Abstract: The findings indicate that, in community-dwelling older people, STS performance is influenced by multiple physiological and psychological processes and represents a particular transfer skill, rather than a proxy measure of lower limb strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
607
12
13

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 800 publications
(660 citation statements)
references
References 30 publications
28
607
12
13
Order By: Relevance
“…Thus, it appears that good vision provides support for safely and quickly undertaking the chair stand test (Lord et al 2002). In this study an independent association between functional vision and chair stand test performance was not found.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Thus, it appears that good vision provides support for safely and quickly undertaking the chair stand test (Lord et al 2002). In this study an independent association between functional vision and chair stand test performance was not found.…”
Section: Resultscontrasting
confidence: 58%
“…The sit-to-stand performance is though influenced by visual function, particularly contrast sensitivity, but there are several other factors associated with the test time, the most important being quadriceps strength (Lord et al 2002). Consequently, in the chair stand test older adults may to some extend better compensate their visual limitations than in the other tests used here.…”
Section: Resultsmentioning
confidence: 93%
“…The impact of physiotherapy on functionality was shown by a faster STSTS performance in the physiotherapy group, already 8 weeks after surgery, and a trend toward a lower ODI-2 score after 1 year. The improvement in proprioceptive use might have determined the faster STSTS performance since this latter task requires postural control (Lord et al, 2002). Furthermore, the association between proprioceptive use and STSTS performance was already observed in non-specific LBP patients (Claeys et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…An essential daily functional activity, which necessitates postural control (Lord et al, 2002), is the sit-to-stand-to-sit (STSTS) task (Dall and Kerr, 2010). In LBP patients, the STSTS task is more energy demanding (Shum et al, 2009) and associated with altered movement patterns (Jacobs et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Performance of the sit-to-stance transfer requires the ability to maintain balance while producing enough muscle force to raise the body's centre of mass from a seated to a standing position (e.g., Schenkman et al 1996;Lord et al 2002). Studies of rising from a chair have demonstrated age eVects on the sit-tostance performance (e.g., Pai and Rogers 1990), and an association of task performance with muscle force in the leg extensors (e.g., Ploutz-Snyder et al 2002).…”
Section: Assessment Of Balance and Gaitmentioning
confidence: 99%